Cash Waqf Models of Baitul Maal wat Tamwil in Indonesia - Ascarya Ascarya; Siti Rahmawati; Raditya Sukmana (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2017)
Cash waqf is one type of contemporary waqf which has been widely applied by waqf institutions and Islamic financial institutions in Muslim majority countries as well as in Muslim minority countries. This study is intended to identify and analyze the cash waqf model applied by three Baitul Maal wat Tamwil (BMT) as certified Nazhir with their unique characteristics, not only to achieve triple bottom-line (outreach, sustainability and welfare impact), strengthen its role as the agent of holistic financial inclusion (HFI) and develop micro enterprises (MEs), but also to improve its social programs, to improve its stability as well as to contribute to financial system stability. The results show that managing cash waqf (direct and indirect) will benefit not only final mauquf alaih (beneficiaries of BMT’s social programs), but also intermediate mauquf alaih (BMT and its MEs members). BMT would benefit from the placement of cash waqf funds in its waqf equity and investment deposit accounts, not only as source of fund, but also provides better liquidity risk and reduce mismatch, which in the long run would improve BMT stability and its resilience to external shock. BMT members and MEs would benefit from cheaper cost of micro-financing. Final mauquf alaih would benefit from more variety and better quality social programs. To improve the participation of BMTs in managing cash waqf, BMT should be authorized and encouraged, with incentives and necessary regulations, to independently manage its own cash waqf collected. Moreover, the determinants of BMT soundness should not only include its Baitut Tamwil performance, but also include its Baitul Maal performance. JEL Classification: D60, G210 Keywords: Waqf, Cash Waqf, Baitul Maal wat Tamwil